INTEGRATION OF PROCESSES IN PEDAGOGICS AND LINGUISTIC SCIENCES - Djalilova Malika Shuxratovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The article presents the survey of social and methodological preconditions, improving the appearance and the improvement of the standards of interdisciplinary combination in the arrangement of advanced education.